3, 5, 4′-tri-O-acetylresveratrol Ameliorates Seawater Exposure-Induced Lung Injury by Upregulating Connexin 43 Expression in Lung. (12th March 2013) - Ma, Lijie; Li, Yanyan; Zhao, Yilin; Wang, Qingwei; Nan, Yandong; Mu, Deguang; Li, Wangping; Sun, Ruilin; Jin, Faguang; Liu, Xueying
Abstract : The aim of the present study was to examine the effects of 3, 5, 4′-tri-O-acetylresveratrol on connexin 43 (Cx43) in acute lung injury (ALI) in rats induced by tracheal instillation of artificial seawater. Different doses (50, 150, and 450 mg/kg) of 3, 5, 4′-tri-O-acetylresveratrol were administered orally for 7 days before modeling. Four hours after seawater inhalation, histological changes, contents of TNF- α, IL-1 β and IL-10, and the expression of Cx43 in lungs were detected. Besides, the gap junction communication in A549 cells and human umbilical vein endothelial cells (HUVECs) challenged by seawater was also evaluated. Histological changes, increased contents of inflammatory factors, upregulation in gene level, and deregulation in protein level of Cx43 in lungs stimulated by seawater were observed. On the other hand, pretreatment with 3, 5, 4′-tri-O-acetylresveratrol significantly inhibited infiltration of inflammation, development of pulmonary edema, and contents of inflammatory mediators in lungs. Above all, 3, 5, 4′-tri-O-acetylresveratrol upregulated the expression of Cx43 in both gene and protein levels, and its intermediate metabolite, resveratrol, also enhanced the gap junction communication in the two cell lines. The results of the present study suggested that administration of 3, 5, 4′-tri-O-acetylresveratrol may be beneficial for treatment of inflammatorycellsin lung.